Phytochemical Profile, Pharmacological Attributes and Medicinal Properties of Convolvulus prostratus – A Cognitive Enhancer Herb for the Management of Neurodegenerative Etiologies - Balkrishna, Acharya; Thakur, Pallavi; Varshney, Anurag (Frontiers in Pharmacology, 2020)
Convolvulus prostratus Forssk., a nootropic herb used in traditional medicinal systems, is also frequently known by its taxonomic synonym Convolvulus pluricaulis. In Indian medicinal system - Ayurveda - it is named as Shankhpushpi. According to the ancient literature, this herb has been attributed with several therapeutic properties, such as anxiolytic, neuroprotective, antioxidant, analgesic, immunomodulatory, antimicrobial, antidiabetic and cardioprotective activities. This medicinal herb has been reported to contain many bioactive phytoconstituents, such as, alkaloid (convolamine), flavonoid (kaempferol) and phenolics (scopoletin, β‑sitosterol and ceryl alcohol), that have been ascribed to the observed medicinal properties. Several research teams across the globe have highlighted the neuro-pharmacological profile of C. prostratus, wherein, the neuroprotective, nootropic and neuro-modulatory roles have been described. Besides, role of C. prostratus extracts in neurodegeneration has been well demonstrated. Despite of such elaborative preclinical pharmacological profile, detailed clinical investigations and mechanistic mode-of-action studies of this important herb are yet to be executed. The present review is attempted to showcase the phytochemical profile, pharmacological attributes and medicinal information of C. prostratus; with comprehensive research gap analysis. It is hoped that the scientific update on the ethnomedicinal aspects of this herb would thrive research propagation and development of the CNS phytopharmaceuticals, originated from C. prostratus.